Polymeric Bimetallic Catalyst-Promoted In-Water Dehydrative Alkylation of Ammonia and Amines with Alcohols - Yamada, Yoichi M. A.; Ohta, Hidetoshi; Yuyama, Yoshinari; Uozumi, Yasuhiro (Synthesis, 2013)
A dehydrative alkylation with three kinds of Ir/B heterobimetallic polymeric catalysts in water is reported. The polymeric heterobimetallic catalysts were readily prepared by ionic convolution of a poly(catechol borate) and iridium complexes. The N-alkylation of ammonia and amines with alcohols, as alkylating agents, was carried out with a heterogeneous catalyst (1 mol% Ir) at 100 °C without the use of organic solvents under aerobic and aqueous conditions to afford the corresponding alkylated amines in high yield.
Keywords: dehydrative alkylation; polymeric boron iridium catalyst; amines; ammonia; alcohols